The Future of Work; Restructuring and Emerging Roles of Human Resource - Ayodeji G. OMOTOLA; Taiye BORISHADE; Marvellous A.C. GBEREVBIE; Oluwakemi O. ONAYEMI; Stanley N. AJALIE (Communications of International Proceedings, 2021)
Being the most important out of the resources for business and organizational growth, the roles of the human resource, managers/management has become even more important since the pandemic as there has been a consequential change in how work is done. This change, which has been aided by the need to keep work going regardless, has been fast tracked by the adoption of technology, which has played a vital role in ensuring almost a seamless operation of business. The ripple effect of restructuring is borne by the workers/employees/human resource, as everyone in the organization needs to adjust to the change that has come to stay. It’s a known fact that change is constant but the process of adopting to this change is tasking and some people fall on the way either due to inability to fit into the new normal (unskilled) or not being able to catch up. This paper adopted a conceptual method; in highlighting measures organizations can put it in place while restructuring, to fit into the future workplace (which is now). Amongst other findings, it was revealed that proper communication is very important and the need to understand the available skills in the workforce and match talent with work much more effectively which would help understand current and potential skills gap.
Keywords: Human resource; organizational change and Restructuring; Future of work; Change management and workplace